Addition of anionic polysaccharides to improve the stability of rice bran protein hydrolysate-stabilized emulsions. (August 2019) - Zang, Xiaodan; Wang, Junwen; Yu, Guoping; Cheng, Jianjun
Abstract: The effects of the addition of different anionic polysaccharides (gum arabic, pectin, xanthan gum and alginate) on the stability of a rice bran protein hydrolysate (RBPH)-stabilized emulsion were investigated. The type and concentration of the polysaccharide have substantial influence on the emulsion stability. Pectin and xanthan gum were better able to stabilize RBPH-coated droplets compared with gum arabic and alginate. Various environmental stresses (salt addition: 0–500 mM NaCl and pH 3.5; thermal processing: 30–90 °C 30 min, 0 mM NaCl, and pH 3.5) were used to test the stability of the emulsions stabilized with pectin or xanthan gum, and their apparent morphology, particle size, ζ-potential and microstructure were used as indicators of stability. The emulsions stabilized by xanthan gum or pectin were stable under all the tested NaCl concentrations. However, under the stress of thermal processing, the emulsion stabilized with xanthan gum shown instability at 90 °C. Polysaccharides improved the stability of the emulsions through increased electrostatic and steric repulsions between the droplets. These results could facilitate the application of rice bran protein as a food additive in the food industry. Highlights: Different anionic polysaccharides improve the stability of RBPH-stabilized emulsions. Pectin and xanthan gum are better able to stabilize the RBPH-coated droplets. Pectin- or xanthan gum-RBPH-stabilized emulsions can tolerate environmental stresses.